Identification and Characterization of a Gene Cluster for Synthesis of the Polyketide Antibiotic 2,4-Diacetylphloroglucinol from Pseudomonas fluorescens Q2-87 - Bangera, M. Gita (American Society for Microbiology, 1999)
The polyketide metabolite 2,4-diacetylphloroglucinol (2,4-DAPG) is produced by many strains of fluorescent Pseudomonas spp. with biocontrol activity against soilborne fungal plant pathogens. Genes required for 2,4-DAPG synthesis by P. fluorescens Q2-87 are encoded by a 6.5-kb fragment of genomic DNA that can transfer production of 2,4-DAPG to 2,4-DAPG-nonproducing recipient Pseudomonas strains. In this study the nucleotide sequence was determined for the 6.5-kb fragment and flanking regions of genomic DNA from strain Q2-87. Six open reading frames were identified, four of which (phlACBD) comprise an operon that includes a set of three genes (phlACB) conserved between eubacteria and archaebacteria and a gene (phlD) encoding a polyketide synthase with homology to chalcone and stilbene synthases from plants. The biosynthetic operon is flanked on either side by phlE and phlF, which code respectively for putative efflux and regulatory (repressor) proteins. Expression in Escherichia coli of phlA, phlC, phlB, and phlD, individually or in combination, identified a novel polyketide biosynthetic pathway in which PhlD is responsible for the production of monoacetylphloroglucinol (MAPG). PhlA, PhlC, and PhlB are necessary to convert MAPG to 2,4-DAPG, and they also may function in the synthesis of MAPG.